2009
DOI: 10.1002/bip.21276
|View full text |Cite
|
Sign up to set email alerts
|

A statistical thermodynamic approach for predicting the sequence‐dependent nucleosome positioning along genomes

Abstract: Nucleosomes are the fundamental repeating unit of chromatin and constitute the structural building blocks of the eukaryotic genome. The distribution of nucleosomes along the genome is a significant aspect of chromatin structure and influences gene regulation through modulation of DNA accessibility. For this reason, an increasing interest is arising in models capable of predicting the nucleosome positioning along genomes. Toward this goal, we propose a theoretical model for predicting nucleosome thermodynamic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…However, the accuracy of these models depends greatly on the quality of the data about the physical properties of DNA loci and the exact influence that these properties have on nucleosome formation. Several studies reported physical models; however, their genome-wide accuracy has not yet been thoroughly investigated (111,118,152,178,182).…”
Section: Cis Determinants Of Nucleosome Positioning Predicting Nucleomentioning
confidence: 99%
“…However, the accuracy of these models depends greatly on the quality of the data about the physical properties of DNA loci and the exact influence that these properties have on nucleosome formation. Several studies reported physical models; however, their genome-wide accuracy has not yet been thoroughly investigated (111,118,152,178,182).…”
Section: Cis Determinants Of Nucleosome Positioning Predicting Nucleomentioning
confidence: 99%
“…Intrinsic DNA sequence preferences of nucleosomes, has been a long-standing question for more than three decades [22][23][24][25][26][27][28]. Yet, a general answer to this question at the genome-wide level is still debated and a matter of active research [5][6][7]10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, experimental mapping of genome-wide nucleosome organization has been obtained for several model systems 33 34 35 36 37 38 , such as Saccharomyces cerevisiae , Caenorhabditis elegans , Drosophila melanogaster and Homo sapiens , but the mechanism of nucleosome positioning still remains elusive. A variety of models have been proposed for predicting nucleosome occupancy that are classified into categories of bioinformatics 19 39 40 41 42 43 44 45 and energetics of nucleosomal DNA 46 47 48 49 50 51 52 53 54 . Bioinformatics models learn various sequence features, such as dinucleotide distributions and oligonucleotide motif frequency from a large quantity of nucleosomes 39 40 41 42 43 .…”
mentioning
confidence: 99%
“…There are a number of energetics models designed to predict nucleosome formation energy, nucleosome occupancy and positions 46 47 48 49 50 51 52 53 54 . A model 51 that took into account the deformations of DNA helical twist, roll and tilt achieved a moderate correlation between its prediction and experimental nucleosome occupancy (R = 0.45, P < 0.0001, on yeast chromosome III).…”
mentioning
confidence: 99%